2008
DOI: 10.7205/milmed.173.9.906
|View full text |Cite
|
Sign up to set email alerts
|

Military and Leisure-Time Noise Exposure and Hearing Thresholds of Finnish Conscripts

Abstract: This study presents an evaluation of the total cumulative noise exposure of Finnish conscripts (N = 416) during military service. All of the conscripts underwent a hearing screening and filled out a noise exposure questionnaire at the beginning and end of their military service. Eighty-nine percent of the conscripts were exposed weekly to military noise of over 85 dBA during the service. Eighteen percent of the conscripts had already reached at the end of their military service a cumulative noise dose correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…This is in accordance with the findings by Jokitulppo et al [19,20] The slightly lower prevalence values in our study, compared to the Finnish one, could be due to the strict hearing inclusion criterion that has been used in Sweden since some years. The increase in prevalence values of HI during the military service seems to be the same in Finland and Sweden, 8-9%.…”
Section: Auditory Symptoms and Hearing Impairmentsupporting
confidence: 94%
See 3 more Smart Citations
“…This is in accordance with the findings by Jokitulppo et al [19,20] The slightly lower prevalence values in our study, compared to the Finnish one, could be due to the strict hearing inclusion criterion that has been used in Sweden since some years. The increase in prevalence values of HI during the military service seems to be the same in Finland and Sweden, 8-9%.…”
Section: Auditory Symptoms and Hearing Impairmentsupporting
confidence: 94%
“…[10] The prevalence values of most auditory symptoms asked for increased from reporting to military service to discharge. Jokitulppo et al, [19] reported the opposite situation with decreasing prevalence values of tinnitus and sensitivity to noise. In our material the participation rate was high both at reporting to service and at discharge.…”
Section: Auditory Symptoms and Hearing Impairmentmentioning
confidence: 96%
See 2 more Smart Citations
“…In our study more than 60% experienced post-exposure tinnitus. Jokitulppo (35) stated that exposure to IN has a correlation to tinnitus. The occurrence of noise related auditory changes depends on exposure type (e.g., sound level, duration, type of noise, and frequency), as well as personal factors (e.g., susceptibility to noise, age, smoking, prior history of hearing/ear damage) (36,37).…”
Section: Discussionmentioning
confidence: 99%